Variation in egg size, fecundity and size structure in female red king crab (Paralithodes camtschaticus, Tilesius 1815) from Varangerfjorden over time. - Høyning, Rasmus Kristoffer (UiT Norges arktiske universitet, 2018)
The introduced red king crab (Paralithodes camtschaticus) has successfully established in Norwegian waters since its release to the Barents Sea in the 1960’s. It has become an important commercial resource contributing to the local coastal society in the eastern region of Finnmark. The fishery consists of one quota regulated area east of 26° (North Cape) and an open fishery west of 26°E. During the years of commercial fisheries multiple changes has been issued in the management regime. Change from a male-only fishery, a lowering of legal catchable sizes in both male and female crabs and quotas for female crabs have been applied with the intention that the red king crab should continue to be an important commercial resource as well as preventing further spreading west of 26°E. It has therefore been of great interest to study the development of the invasive red king crab. This study looks at fecundity, egg size and ovigerous female size distribution in Varangerfjorden in the period 2008-2017, comparing it with a previous study from the period 2000-2007 by Hjelset et al., (2012). The size-distribution of ovigerous females has changed as there are almost no big females > 150 mm left in the population. Individuals of 110-120 mm make up the biggest part of the ovigerous females population. Fecundity was found to be a function of size (p < 0.0001) and individual egg weight was not a function of size (p > 0.05). A mean sized female of 117 mm has increased number of spawning events by 20% based on lower calculated OL50-values in the recent years. The fecundity upper range has declined due to the disappearance of the biggest females and therefore the potential egg production of the stock has declined. To maintain sustainable management, it is important to monitor the reproductive features such as fecundity, as it gives information about its reproductive potential. Thus, more work needs to be done to fully understand the reproductive biology of the red king crab in Norwegian waters.